Analysis of Using Social Networks in Promoting University Educational Services - G. A. Konopyanova; Zh. Y. Baikenov; A. A. Mambetkaziyev; Z. S. Mukhambetova (Экономика: стратегия и практика)
The article is devoted to studying the promotion of university educational services in the digital environment and developing recommendations for increasing the effectiveness of this area of their marketing activities. A review of the literature and the use of general and unique methods of scientific cognition made it possible to clarify the role of Internet tools in the communication patterns of a modern university and determine groups of external and internal target audiences. It has been established that the primary means of university digital media communication are the website and social networks. An analysis of the digital profiles of universities on websites made it possible to identify shortcomings related to both the content and the technical side: problems with updating and duplicating information, non-compliance with the sequence of stages of the sales funnel, restrictions on access to information, difficulty in navigation, and lack of mobile versions. Audit and content analysis of university social networks were conducted using quantitative and qualitative indicators. Quantitative analysis revealed the most significant demand for such platforms as Instagram and Facebook. The quality of using social networks as promotion tools is reduced due to the lack of corporate identity and poor consideration of the interests and needs of the target audience. The authors compiled SWOT-analysis of strengths and weaknesses, opportunities and threats of Internet resources of Kazakhstan universities and proposed stages, structure and content of the strategy for promoting university educational services in the digital environment.